(3GdYjfs - (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efgG ef bHd (B" (3HGH GdKdGKi GdUMjM (B" 6 (3ef MQa GdYjf bhdg GdLOY (B: (3bWY GdCfa hGdCPf hGdTaI s
(3BNQgG (B:s
(3BNQ GdehLhO efgG ef (B" (3HGH GdKdGKi GdeYJd (B" [ (3ef MQa GdOGd (B] (3, bhdg (B: (3QLd eaFhO bO CUGH aDGOg OGA GdhGaO (B: (3GdQShd Edi Gdedc , hGdLeY GdhaO hGdOha NdW GdRYaQGf s
(3fSNI KGfjg bWYI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B158 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GddZIs